Afghanistan’s Renewable Energy Landscape: Addressing Challenges, Policy Framework, and Recommendations (Salam International Academic Journal, 2023)
Afghanistan, a developing nation, aims to generate 10 percent of its electricity from renewable sources by 2032 to overcome challenges like imported electricity dependency, rural electrification gaps, and environmental degradation. This paper offers a comprehensive review of Afghanistan's renewable energy landscape, including potential, current capacity, and future plans through utilizing secondary data collection methods. Despite abundant renewable energy potential in hydropower, solar, wind, and biomass, challenges like unclear policies, limited expertise, security risks, and public engagement barriers persist. To address these hurdles, a clear national renewable energy policy, enhanced institutional capacity, and public-private partnerships are crucial. Overcoming these challenges can help Afghanistan achieve its renewable energy goals, while also fostering peacebuilding, state-building, and climate change mitigation.
Keywords: Afghanistan; capacity building; renewable energy; energy access; electricity; energy policy